Upaya Meningkatakan Minat Belajar Siswa pada Pembelajaran Matematika Melalui Penggunaan Media konkret pada Siswa Kelas III di SDN 110/1 Tenam - Hilda Afrina; Nasyariah Siregar (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This thesis discusses efforts to increase students’ interest in learning Mathematics through the use of concrete media among third-grade students at SDN 110/1 Tenam. The purpose of the study is to improve students’ interest in learning Mathematics by using concrete media with these third-grade students. The results of the study show an increase in learning activities that indicate student interest during Cycle I and Cycle II. In Cycle I, all student learning activities were still at percentages below 70%, with ratings categorized as poor and adequate. Meanwhile, in Cycle II, the increase in student learning activities was shown by all activities reaching percentages above 74%, which means they exceeded the predetermined Learning Objectives Achievement Criteria (KKTP) and were rated good and very good. In addition, improved learning outcomes, as evidence of increased student interest, also showed a significant rise. In Cycle I, students’ learning outcomes did not meet the Learning Objectives Achievement Criteria (KKTP), with a class average of 68.9%, whereas in Cycle II, overall class mastery reached 82.3%. This improvement in learning outcomes indicates that students showed fairly good interest when learning with concrete media.